The rotational elements of Mars and its satellites. (March 2018) - Jacobson, R.A.; Konopliv, A.S.; Park, R.S.; Folkner, W.M.
Abstract: The International Astronomical Union (IAU) defines planet and satellite coordinate systems relative to their axis of rotation and the angle about that axis. The rotational elements of the bodies are the right ascension and declination of the rotation axis in the International Celestial Reference Frame and the rotation angle, W, measured easterly along the body's equator. The IAU specifies the location of the body's prime meridian by providing a value for W at epoch J2000. We provide new trigonometric series representations of the rotational elements of Mars and its satellites, Phobos and Deimos. The series for Mars are from a least squares fit to the rotation model used to orient the Martian gravity field. The series for the satellites are from a least squares fit to rotation models developed in accordance with IAU conventions from recent ephemerides. Highlights: An IAU conforming trigonometric series representation of the rotational elements of Mars is provided. An IAU conforming trigonometric series representation of the rotational elements of Phobos is provided. An IAU conforming trigonometric series representation of the rotational elements of Deimos is provided.